Perceptions of mental disorder causes, treatments, and prevention among the general population in Saudi Arabia - Senitan, Mohammad; Alhabeeb, Abdulhameed Abdullah; Althumairi, Nora A.; Alqahtani, Mohammed M. J.; Al-Duraihem, Rashed Abdullah; BinDhim, Nasser F. (Frontiers in Psychiatry, 2024)
This study investigates the community’s perception of mental health in Saudi Arabia, emphasizing its influence on attitudes toward the causes, treatment, and prevention of mental health issues. This understanding is vital for creating evidence-based mental health interventions. A cross-sectional national mental health screening was conducted in 2023, utilizing proportional quota sampling for age, gender, and regional representation among 4547 Saudi participants aged 18–90, randomly selected from national databases. Data were gathered using the ZDataCloud system. The study covered all 13 administrative regions of Saudi Arabia: Riyadh, Makkah, Madinah, Qassim, Eastern Province, Asir, Tabuk, Hail, Northern Borders, Jazan, Najran, Baha, and Al-Jouf. The majority (86.5%) had no personal history of mental health diagnosis or treatment. Key findings identified psychological trauma (78.36%) and substance abuse (72.88%) as primary perceived causes of mental disorders. Preferred treatments included non-pharmacological psychotherapies (74.97%) and pharmacological methods (71.08%). Prevention strategies focused on raising awareness of mental illness (80.4%) and enhancing positive relationships (70.6%). A multivariate logistic regression analysis revealed significant associations between demographic variables and perceptions of mental disorder causes, treatments, and prevention strategies. Females were more likely than males to perceive psychological trauma, drug and alcohol abuse, and domestic violence and sexual harassment as causes of mental disorders. Regarding treatments, females and those with personal or close connections to mental health issues were more likely to endorse non-pharmacological psychotherapy and Roquia in the Qur’an. For prevention strategies, females, those with a mental health diagnosis, and those living with someone diagnosed with a mental disorder were more likely to endorse increasing awareness, positive social relationships, and physical activity. The study suggests integrating religious and social beliefs into mental health programs to enhance community engagement and effectiveness.